Investigating the relationship between temperature, conformation and calcium binding in heparin model oligosaccharides. (13th January 2017) - Hughes, Ashley; Meneghetti, Maria; Huang, Teng-Yi; Hung, Shang-Cheng; Elli, Stefano; Guerrini, Marco; Rudd, Timothy; Lima, Marcelo; Yates, Edwin
Abstract: Glycosaminoglycans such as heparan sulfate (HS) are major components of the cell surface and extracellular matrix (ECM) of all multicellular animals, connecting cells to each other as well as to their environment. The ECM must, therefore, both sense and accommodate changes to external conditions. Heparin, a model compound for HS, responds to increased temperatures, involving changes in the populations of conformational states with implications for the binding of HS to proteins, cations and, potentially, for its activity. A fully 13 C and 15 N labelled model octasasccharide; D-GlcNS6S α(1-4) L-IdoA2S [α(1-4) D-GlcNS6S α(1-4) L-IdoA2S]2 α(1-4) D-GlcNS6S α(1-4) L-IdoA1, 6an, was studied by 1 H, 13 C and 15 N NMR, revealing complex changes in chemical shifts and conformation, over temperatures (280–305 K), comfortably within the range relevant to terrestrial biology. These complex conformational changes indicated an interaction between the carboxylate group of L-iduronate and D-glucosamine residues that was susceptible to temperature changes in this range, while the well-documented hydrogen bond between the N -sulfamido group of glucosamine and the hydroxyl group at position-3 of iduronate remained intact. Unexpectedly, despite the presence of similar thermally-induced conformational changes in a heparin octasaccharide fraction in the sodium ion form, its subsequent binding to calcium ions and their resulting conformation was stringently maintained, as judged by comparisons of 1 H NMR chemical shifts. Graphical abstract: Highlights: 13 C/ 15 N labelled heparin octasasccharide was studied by 1 H, 13 C & 15 N NMR. Complex chemical shift changes were observed from 280 to 305 K. A new thermally-sensitive interaction was identified. Ca binding to heparin was maintained regardless of conformational state.